Nitrogen cycling in monospecific and mixed-species plantations of Acacia mangium and Eucalyptus at 4 sites in Brazil - Voigtlaender, M.; Brandani, C. B.; Caldeira, D. R.M. [UNESP]; Tardy, F.; Bouillet, J. P.; Gonçalves, J. L.M.; Moreira, M. Z.; Leite, F. P.; Brunet, D.; Paula, R. R.; Laclau, J. P. [UNESP] (Elsevier, 2019)
Mixing N-fixing trees with eucalypts is an attractive option to improve the long-term soil N status in fast-growing plantations established in tropical soils. A randomized block design was replicated at four sites in Brazil to compare the biogeochemical cycles in mono-specific stands of Eucalyptus (100E) and Acacia mangium (100A) with mixed-species plantations in a proportion of 1:1 (50A50E). Our study aimed to assess the effects of introducing A. mangium trees in Eucalyptus plantations on atmospheric N 2 fixation, N cycling and soil organic matter stocks. Litterfall and soil N mineralization were measured over the last two years of the rotation (4–6 years after planting). Aboveground N accumulation in the trees and C and N stocks in the forest floor and in the top soil were intensively sampled at harvesting age. N 2 fixation rates were estimated using the natural abundance of 15 N as well as by the difference between total N stocks in 100A and 50A50E relative to 100E (accretion method). While the 15 N natural abundance method was unsuitable, the accretion method showed consistently across the four sites that atmospheric N fixation reached about 250 and 400 kg N ha −1 rotation −1 in 50A50E and 100A, respectively. Except at one site with high mortality, N contents within trees at harvesting were approximately 40% higher in 100A than in 100E. Mean N contents in litterfall and N mineralization rates were about 60% higher in 100A than in 100E, with intermediate values in 50A50E. The amounts of N in litterfall were much more dependent on soil N mineralization rates for acacia trees than for eucalypt trees. Soil C and N stocks were dependent on soil texture but not influenced by tree species. N budgets over a 6-year rotation were enhanced by about 65 kg N ha −1 yr −1 in 100A and 40 kg N ha −1 yr −1 in 50A50E relative to monospecific eucalypt plantations. Introducing N-fixing trees in eucalypt plantations might therefore contribute to reducing the need for mineral N fertilization in the long-term.
Keywords: Eucalypt; Litterfall; N 2 fixation; Nutrition; Organic matter; Tree mixtures; Tropical plantations